The Influence of Nanoparticles of Graphene Oxide‑PEG on Cytokine Profile of Monocytes from Human Blood In Vitro - D.I., Usanina; M.S., Bochkova; V.P., Timganova; K.Yu, Shardina; S.A., Zamorina; M.B., Rayev (Trends in Immunotherapy, 2025)
This study investigated the response of human monocytes to co-culture with pegylated (linear or branched) graphene oxide (GO) nanoparticles, specifically examing both small (P-GOs, 100 -200 nm) and larger (P-GOb, 1-5 μm) particles at concentrations of 5, 25, and 50 µg mL–1. Human monocytes (CD14+ cells) were isolated and cultured with these nanoparticles for 72 hours. We measured cell viability, lactate dehydrogenase (LDH) release, and cytokine production. The findings showed that P-GO nanoparticles had little effect on cytokine production, including MIF, GM-CSF, VEGF, IP-10, IL-8, HGF, and SCGF-beta in vitro. At a low concentration (5 μg mL–1), P-GO exhibited minimal influence on cytokines, except forthe LP-GOb variant, which increased M-CSF production. Conversely, 25 and 50 μg mL–1 of P-GO nanoparticles enhanced the release of variouscytokines, including proinflammatory IL-6, IL-1β, IL-1α, IL-18, IL-17, IL-16, IFN-γ, TNF-β, TNF-α, anti-inflammatory IL-1ra, IL-13, IL-10, IL-4, regulatory G-CSF, IL-2, IL-3, IL-5, IL-12 (p40), IL-12 (p70), M-CSF, GM-CSF and chemokines CTACK, Eotaxin, GRO-α, RANTES, MIP-1β, MCP-1, MIP-1α, MCP-3, MIG, SDF-1α, growth factors Basic FGF, PDGF-BB, SCF, and LIF and TRAIL. Although higher concentrations of P-GO nanoparticles resulted in significant cytokine production, monocyte viability remained largely unaffected . LDH release was elevated solely in samples treated with 50 μg mL–1 of LP-GOb. BP-GOs showed minimal influence on cytokine profiles, raising M-CSF levels at the highest concentration. These results indicate that modifying graphene oxide nanoparticles may hold potential for creating graphene-based pharmacological agents.